HOW THE MODIFICATION OF UNESCO GLOBAL GEOPARK PROGRAM INFLUENCED JAPANESE GEOPARKS - Fujii, Ikuno; Ito, Hiromu (PEOPLE: International Journal of Social Sciences, 2020)
This study attempts to clarify how international discussions related UNESCO Global Geoparks were reflected in the geopark program in Japan by examining movements and discussions of international and regional organizations which took roles for the establishment of geopark initiatives, focusing up to 2015 when UNESCO officially launched the program. The process up to the establishment of UNESCO Global Geopark was divided into four stages including “geopark random activity period” which various international organizations committed its own “geopark activities”, and followed to “geopark integration period” which those activities integrated as one geopark program under UNESCO and all of them happened in less than 20 years. In Japan, geologists started domestic geopark program influenced by the international geopark movements. The time when they started and expanded geopark activities in Japan happened parallel to the “geopark random activity period” in international society. As a result, the geopark system in Japan resulted in emphasizing geological features compared to UNESCO Global Geoparks in terms of its evaluation and management even though Japan Geopark Committee take efforts to aim for the holistic geopark implementation in accordance with UNESCO Global Geoparks policy. This conclusion suggests a regional confusion due the fact that geopark as an international program changed its framework within a short period.